Strategi Pemasaran untuk Meningkatkan Omset Penjualan pada UMKM Pawon Prima Karawang - Febrian, Dio; Citra Savitri; Syifa Pramudita Faddila (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze the marketing strategies implemented by Pawon Prima Karawang to increase sales turnover of its products, specifically PAPRIKA fried peanuts. The research method used was descriptive qualitative, with data collected through interviews, observation, and documentation, as well as source triangulation to gain in-depth understanding. The results indicate that the implemented marketing strategies include managing quality products, pricing according to market segments, promotions through social media and e-commerce, distribution through resellers and distributors, improving service quality through employee training, and providing tangible evidence in the form of attractive packaging and product certification. This strategy successfully increased Pawon Prima Karawang's sales turnover from 90 million rupiah in 2021 to 147 million rupiah in 2023. The conclusion of this study states that the implementation of a comprehensive, integrated marketing strategy significantly contributed to increasing sales turnover and the development of Pawon Prima Karawang's MSME business.   Keywords: Marketing Strategy, Sales Turnover, Development